INTERPRETING A POEM OF BEN JONSON, “SONG: TO CELIA” - Nanik Mariana Effendie (LET: Linguistics, Literature and English Teaching Journal)
ABSTRACT Discourse analysis is analysis of language in use (Brown and Yule, 1983). How the language-users interpret what other language-users intend to convey and how they make sense of what they read in texts, understand what speakers mean despite what they say, recognize connected as opposed to jumbled or incoherent discourse, and successfully take part in that complex activity called conversation.